Tandem 1, 6-addition/cyclopropanation/rearrangement reaction of vinylogous para-quinone methides with 3-chlorooxindoles: construction of vicinal quaternary carbon centers. Issue 14 (5th June 2022) - Pan, Yuan; Ren, Weiwu; Zhang, Zhanhao; Luo, Fengbiao; Hou, Xiaohan; Li, Xiaoyang; Yang, Yun-Fang; Wang, Yang
Abstract : A novel tandem 1, 6-addition/cyclopropanation/rearrangement reaction of vinylogous para -quinone methides with 3-chlorooxindoles has been developed, providing dispirooxindole–cyclopentane–cyclohexadienones with vicinal quaternary carbon centers. Abstract : A novel tandem 1, 6-addition/cyclopropanation/rearrangement reaction of vinylogous para -quinone methides with 3-chlorooxindoles is reported. This method provides an efficient approach to various functionalized dispirooxindole–cyclopentane–cyclohexadienones with vicinal quaternary carbon centers. Computational studies have been conducted to provide insight into the origin of diastereoselectivity and predict a stepwise diradical mechanism. The anti-tumor activities of these structurally unique dispirooxindole derivatives are also reported.